Pelatihan penguatan ekonomi lokal berbasis smart economy pada Desa Sukajadi - Muaraenim: Training on strengthening the local economy based on smart economy in Sukajadi - Muaraenim Village - Andriyani , Titi; Miskiyah, Neneng; Andriyani, Titi; Purwati, Purwati (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT Strengthening the family economy is carried out to reduce poverty levels and improve the welfare of the community. Strengthening the economy in a region is expected to increase community productivity. Strengthening the family and regional economy can be done by using the concept of a smart economy, which combines sustainable, environmentally friendly and innovative economic approaches, including high-productivity economies, global economic growth, competition, economic progress, economic prosperity, innovation, sustainable employment, and the digital economy. The purpose of this community service is to increase the insight of Doyan Ngemil Chips Business Owners about how to innovate and be creative in marketing their products by utilizing the availability of human resources and raw material resources available in the community as well as utilizing website-based information technology in promoting and marketing their products. The training methods used are tutorial methods, question and answer methods, and practice methods. The result of this service is that the participants understand the material that has been presented by the Sriwijaya State Polytechnic Service Team and can use/practice how to use the Website application properly. Conclusion: This training activity ran smoothly and according to what was planned. If in the future there are obstacles or shortcomings in the application that has been made, the team from the Police will discuss with the participants to correct the existing shortcomings. Keywords: Digital Economy; Family Economy; Innovation; Marketing; Smart Economy ABSTRAK Penguatan ekonomi keluarga dilakukan untuk mengurangi tingkat kemiskinan dan meningkatkan kesejahteraaan masyrakat. Penguatan perekonomian di suatu daerah diharapkan akan meningkatan produktivitas masyarakat. Penguatan ekonomi keluarga dan daerah bisa dilakuan dengan menggunakan Konsep ekonomi cerdas yaitu menggabungkan pendekatan ekonomi berkelanjutan, ramah lingkungan dan inovatif, termasuk ekonomi dengan produktivitas tinggi, pertumbuhan ekonomi global, persaingan, kemajuan ekonomi, kemakmuran ekonomi, inovasi, lapangan kerja berkelanjutan, dan ekonomi digital. Tujuan dari pengabdian kepada masyarkat ini adalah menambah wawasan Pemilik Usaha Keripik Doyan Ngemil mengenai cara berinovasi dan berkreativas dalam memasarkan produk-produknya dengan memanfaatkan ketersediaan sumber daya manusia dan sumber daya bahan-bahan baku yang tersedia di lingkungan masyarakat serta memanfaatkan teknologi informasi berbasis website dalam mempromosikan dan memasarkan produk-produknya. Metode pelatihan yang digunakan adalah metode tutorial, metode tanya jawab, metode praktik. Hasil dari pengabdian ini adalah para peserta mengerti tentang materi yang telah dipaparkan oleh Tim Pengabdian Politeknik Negeri Sriwijaya dan dapat menggunakan/mempraktekkan cara menggunakan aplikasi Website dengan baik. Kesimpulan: Kegiatan pelatihan ini berjalan dengan lancar dan sesuai dengan apa yang direncanakan. Apabila dikemudian hari ada kendala atau kekurangan pada aplikasi yang sudah dibuat maka Tim dari Polsri akan melakukan diskusi dengan para peserta untuk memperbaiki kekurangan-kekurangan yang ada. Kata kunci: Ekonomi Cerdas; Ekonomi Digital; Ekonomi Keluarga; Inovasi; Pemasaran